Association Between Perceived Stress and Coagulation Function in Patients With Coronary Heart Disease Admitted to a Tertiary Care Hospital - Chanda, Iram; Ibrahim, Khalida; Bhatti, Fozia Karamat (Biological and Clinical Sciences Research Journal, 2025)
Coronary heart disease (CHD) is a major global health burden, often exacerbated by psychosocial factors such as stress. Emerging evidence suggests that perceived stress may influence coagulation parameters, potentially contributing to adverse cardiovascular outcomes. However, data from low- and middle-income countries, including Pakistan, remain limited. Objective: The objective of the study was to determine the association between perceived stress and coagulation function in patients with coronary heart disease admitted to a tertiary care hospital. Methods: It was a cross-sectional study, conducted at Shaikha Fatima Institute of Nursing and Health Sciences, Lahore, between May to December 2022. Three hundred and ten (310) patients of coronary heart disease were included in the study, a predesigned proforma containing information related to demographic characteristics, medical history, coagulation profile, and perceived stress scale. Results: 310 patients with coronary heart disease participated in our study; their mean ± SD of age, BMI, and monthly income were 52.8±14.2 years, 23.5±7.2, and 65000±20000 rupees, respectively. Among study subjects 298(96.1%) were married 189(61.0%) had sedentary occupation 198(63.8%) were diabetic, 269(86.7%) were hypertensive,112(36.1%) were smokers, obesity was observed in 98(31.6%), 34.8% were physically inactive and 129(41.6%) had family history of cardiovascular disease.. Among 310 subjects 174(56.2%) had perceived stress (score<16) and 136(43.8%) didn’t have perceived stress (score≤16). Coagulation function (APTT) was assessed; 191(61.6%) had deranged (shortened APTT, i.e., <35 sec) coagulation function, and 119(38.4%) had normal coagulation function. In our study significant association was found between perceived stress and coagulation function in patients with coronary artery disease, P=0.000. Conclusion: Perceived stress is strongly associated with PT and APTT regardless of the type of CHD. The negative impact of high perceived stress on cardiovascular prognosis could partially be explained by the activation of the intrinsic coagulation pathway.